‘Lettres de fuite’. Skrift og brud i À la recherche du temps perdu - Watt, Adam (Passage - Tidsskrift for litteratur og kritik, 2015)
Adam Watt: “‘Lettres de fuite’: Writing and Rupture in In Search of Lost of Time” In Marcel Proust’s novel, In Search of Lost Time, the writing and sending of letters, their anticipation and receipt, are activities fuelled by desirous energies and fraught with anxiety and uncertainty. In this paper I consider a number of scenes in which the writing and sending of letters is prompted by the break-up or threatened rupture of an amorous relationship. The sending of missives is an activity bound up with attitudes to communication, otherness, and to futurity. These issues, the emotions they provoke and the epistemological schemes the protagonist develops to deal with them are at the heart of my paper. I compare how letters of rupture figure in the Narrator’s early relationship with Gilberte and in his later relations with Albertine. Exploring the nexus of concerns associated with writing and rupture in Proust’s novel provides an intriguing angle from which to review the Narrator’s relation to temporality and the ways in which Proust figures thought and emotion in the text of the novel.